ИСПОЛЬЗОВАНИЕ СЕМЯН ЧИА В СОСТАВЕ ДИЕТАРНЫХ ПОЛУФАБРИКАТОВ МЯСНЫХ ПРОДУКТОВ - Голембовская, Наталья (Modern scientific researches, 2018)
The article deals with the results of sensory analysis of semi-finished minced fish products with non-traditional raw materials (chia seeds) by the flavor profile method, and establishing their compliance with the hypothetical standard.